2006
DOI: 10.1177/1077727x06286418
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adolescents' Brand Sensitivity to Clothing

Abstract: The objective of this research was to better understand the interest of adolescents in clothing brand names and to ascertain how different psychological, social, and socioeconomic variables explained variance in their brand sensitivity. Multiple linear regression analysis revealed that susceptibility to peer influence, gender, fashion innovativeness, consumer competence, self‐esteem, brand importance for father, and age were significantly related to brand sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 63 publications
5
59
1
3
Order By: Relevance
“…Additionally, female consumers more than male consumers appear to be more interested in clothing and fashion (Beaudoin & Lachance, 2006;Haynes, Burts, Dukes, & Cloud, 1993). Based on these findings, the present study posits:…”
Section: Gender and Fashion Innovativenessmentioning
confidence: 72%
See 3 more Smart Citations
“…Additionally, female consumers more than male consumers appear to be more interested in clothing and fashion (Beaudoin & Lachance, 2006;Haynes, Burts, Dukes, & Cloud, 1993). Based on these findings, the present study posits:…”
Section: Gender and Fashion Innovativenessmentioning
confidence: 72%
“…Recent empirical studies (Beaudoin et al, 2003;Beaudoin & Lachance, 2006) have examined the relationship between fashion innovativeness and brand sensitivity.…”
Section: Fashion Innovativeness and Brand Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research (that did not examine risk related to purchasing apparel) found that women (compared with men) are more open to uncertain and unstructured contexts (Maio & Esses, 2001;Washburn, Smith, & Taglialatela, 2005), are disinclined to take risks (e.g., Wagner, 2001) or that men and women did not differ in tendency for risk taking (e.g., Maxfield et al 2010). Research has found that women score higher than men on brand sensitivity (Beaudoin & Lachance, 2006;Warrington & Shim, 2000) and brand consciousness (Workman & Lee, 2013).…”
Section: Gender and Consumer Behaviourmentioning
confidence: 99%